Regional health economies and ICT services : the PICNIC experience - Saranummi, Niilo (Studies in health technology and informatics, 2005)
Aim to make the European market for telematic healthcare services more cohesive and less fragmented, by developing a model for the preparation of the regional healthcare providers to implement the next generation of secure, user-friendly healthcare networks. It paves the way towards the development of regional healthcare networks.